2015
DOI: 10.1542/peds.2015-0995
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography and Shifts to Alternate Imaging Modalities in Hospitalized Children

Abstract: Many studies have demonstrated a rise in computed tomography (CT) utilization in children's hospitals. However, CT utilization may be declining, perhaps due to awareness of potential hazards of pediatric ionizing radiation, such as increased risk of malignancy. The objective is to assess the trend in CT utilization in hospitalized children at freestanding children's hospitals from 2004 to 2012 and we hypothesize decreases are associated with shifts to alternate imaging modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Advanced diagnostic imaging remains common for patients with suspected appendicitis, 28 with upwards of 80% undergoing ultrasound, CT, or MRI. 29 The decline in use of CT is significant because fewer children are exposed to ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced diagnostic imaging remains common for patients with suspected appendicitis, 28 with upwards of 80% undergoing ultrasound, CT, or MRI. 29 The decline in use of CT is significant because fewer children are exposed to ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cross-sectional study performed across 33 units reported notable reductions in the use of CT scanning in paediatric population for a variety of medical presentations, including an increase in the use of USS and MRI in patients with ventricular shunts. Whilst this is a positive step, CT scanning remained the most common imaging modality [23].…”
Section: Discussionmentioning
confidence: 99%
“…Although it was not the objective of this study, the costs of radiography versus ultrasound is only mentioned but not analyzed. In conclusion, substituting an imaging modality that does not use ionizing radiation may affect lifetime cancer risk in children who receive diagnostic imaging and should be encouraged (7). This study is in the right trend, but a larger multicentric one is lacking and would be of great interest.…”
mentioning
confidence: 89%